A survey of knowledge‐based sequential decision‐making under uncertainty. Issue 2 (23rd June 2022) - Zhang, Shiqi; Sridharan, Mohan
Abstract: Reasoning with declarative knowledge (RDK) and sequential decision‐making (SDM) are two key research areas in artificial intelligence. RDK methods reason with declarative domain knowledge, including commonsense knowledge, that is either provided a priori or acquired over time, while SDM methods (probabilistic planning [PP] and reinforcement learning [RL]) seek to compute action policies that maximize the expected cumulative utility over a time horizon; both classes of methods reason in the presence of uncertainty. Despite the rich literature in these two areas, researchers have not fully explored their complementary strengths. In this paper, we survey algorithms that leverage RDK methods while making sequential decisions under uncertainty. We discuss significant developments, open problems, and directions for future work.